Composition and capacity of Institutional Review Boards, and challenges experienced by members in ethics review processes in Addis Ababa, Ethiopia: An exploratory qualitative study. Issue 1 (5th March 2022) - Seralegne, Yemisrach Zewdie; Wangamati, Cynthia Khamala; Bernabe, Rosemarie D. L. C.; Farsides, Bobbie; Aseffa, Abraham; Zewdie, Martha
Abstract: Few studies in sub‐Saharan Africa evaluate Institutional Review Boards (IRBs) capacity. The study aims to explore the composition of IRBs, training, and challenges experienced in the ethics review processes by members of research institutions and universities in Addis Ababa, Ethiopia. Our findings indicate that most IRBs members were trained on research ethics and good clinical practice. However, majority perceived the trainings as basic. IRB members faced several challenges including: investigators wanting rapid review; time pressure; investigators not following checklists; limited expertise in reviewing clinical trials, studies on genetics, and traditional medicine; lack of IRB offices for administrative work; competing tasks; limited staffing and the lack of a standardized review system. There is need for advanced training on research ethics to meet the evolving research needs. In addition, investments in IRBs are needed in terms of funding, and physical and human resources in Addis Ababa and Ethiopia in general.